Partial economic evaluation of clinical pharmacy interventions on the prescription of direct oral anticoagulants in a teaching hospital. Issue Volume 25:Issue e1(2018) (2nd January 2017) - Declaye, C; Sennesael, A L; Larock, A S; Spinewine, A; Krug, B
Abstract : Background: Potential inappropriate use of direct oral anticoagulants (DOACs) increases the risk of thromboembolic and haemorrhagic events. Purpose: To determine the net cost benefit of clinical pharmacy interventions on the prescription of DOACs. Method: We constructed a decision tree model using a public payer perspective. The appropriateness of the prescription was assessed using the Medication Appropriateness Index. The theoretical risks were collected from the literature and the individual potential risks were calculated using the Nesbit risk assignment conducted by two independent clinical pharmacists. Different costs were included based on diagnosis-related group coding and data in the literature. A univariate sensitivity analysis was performed. Results: Thirty-six of 75 patients had an inappropriate prescription of DOACs. The saved difference between avoided costs (7954€) and annualised medication costs and pharmacist cost (4323€) was 3631€ for 75 patients. Conclusions: In addition to the enhancement of the quality of the prescription, our results indicate that pharmacist interventions provide a positive net cost benefit.